Anti-IL-22 Antibody Attenuates Acute Graft-versus-Host Disease via Increasing Foxp3+ T Cell through Modulation of CD11b+ Cell Function - Jianbo Wu; Jian Gu; Shun Zhou; Hao Lu; Yunjie Lu; Ling Lu; Xuehao Wang (Journal of Immunology Research)
Transfer of splenocytes isolated from B6 mice into normal B6D2F1 mice induces acute graft-versus-host disease (aGVHD), resulting in the expansion of donor cytotoxic T lymphocytes that eliminate recipient B cells. The cytokine IL-22, secreted by Th1 cells, Th17 cells, and innate immune cells, is structurally related to IL-10. To investigate the association between IL-22 and aGVHD, an anti-mouse IL-22 antibody (IL-22Ab) was used to ablate IL-22 activity in a mouse aGVHD model. Administration of IL-22Ab significantly reduced the progression of aGVHD in B6D2F1 recipients of B6 grafts. IL-22Ab treatment also decreased the percentage of interferon-γ+ and tumor necrosis factor-α+ T cells but increased the number of forkhead box p3+ regulatory T cells (Tregs). In the presence of Tregs and donor CD11b+ cells, IL-22Ab protected against aGVHD. In vitro Treg induction was more efficient when CD4+CD25− T cells differentiated in the presence of CD11b+ cells obtained from IL-22Ab-treated GVHD mice, compared with cocultured untreated control cells. Finally, IL-22Ab modulated the expression of cytokines and costimulatory molecules in CD11b+ cells in aGVHD mice. We therefore conclude that IL-22Ab administration represents a viable approach for treating aGVHD.